Reflections on STS in Mainland China: A Historical Review. Issue 2 (1st June 2018) - Li, Zhengfeng; Lu, Xiao
Abstract: This article examines the historical development of the study of science, technology, and society (STS) in China in relation to the features of contemporary Chinese society and the influence of Marxism tradition, the opening up of China, the system reform, and the evolving state of science and technology (S&T) and its history and cultural tradition. Marxism, especially natural dialectics, had a profound impact on China's STS knowledge system, research team, and disciplinary building. Since 1978, with the opening up of China, Western theories about the sociology of science have been introduced into China and have formed an ever-changing relationship with Marxism (natural dialectics). The system reform in China not only raised questions for STS scholars but also provided an opportunity to rethink relevant STS issues and possibilities for participatory research. At the same time, the conditions of China as an evolving state in S&T—along with its history, cultural traditions, and the particularity of Chinese society—have raised additional intriguing questions for STS research. This article considers the relationship and the paradox between Marxism and Western academic tradition, the object and nature of STS study, as well as the significance of STS research in East Asia and China.